2020
DOI: 10.1177/0265407520962849
|View full text |Cite
|
Sign up to set email alerts
|

Putting me back together by getting back together: Post-dissolution self-concept confusion predicts rekindling desire among anxiously attached individuals

Abstract: Previous research suggests that romantic relationship dissolution diminishes self-concept clarity, leading to emotional distress. Over time, people overcome breakup. But little is known about how people respond to the reduced self-concept clarity that results from this process. The current research examined predictors and mediators of relationship rekindling (desiring to reestablish a relationship with an ex-partner) as a method of navigating self-concept clarity impairment post-dissolution. In two cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Couple relationships are less stable than in the past, with an overall growth in divorces over the last three decades (Fine and Harvey, 2006;Reynolds and Profile, 2020). Research has extensively shown that relationship dissolutions may lead to emotional dysregulation and distress, as well as the adoption of dysfunctional behaviors (e.g., insistent telephone calls and text messages, verbal threats, and sending unwanted objects) toward the former partner which can result in severe, debilitative, and, in some situations, life-threatening consequences (Gasbarrini et al, 2015;Curtis et al, 2017;Lee et al, 2020;Cope and Mattingly, 2021;Senkans et al, 2021). Many studies have focused on the long-term consequences of separations and divorces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Couple relationships are less stable than in the past, with an overall growth in divorces over the last three decades (Fine and Harvey, 2006;Reynolds and Profile, 2020). Research has extensively shown that relationship dissolutions may lead to emotional dysregulation and distress, as well as the adoption of dysfunctional behaviors (e.g., insistent telephone calls and text messages, verbal threats, and sending unwanted objects) toward the former partner which can result in severe, debilitative, and, in some situations, life-threatening consequences (Gasbarrini et al, 2015;Curtis et al, 2017;Lee et al, 2020;Cope and Mattingly, 2021;Senkans et al, 2021). Many studies have focused on the long-term consequences of separations and divorces.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that individuals who are divorced tend to report lower levels of psychological and physical well-being, as well as social isolation and economic difficulties (Ross, 1995 ; Pinquart, 2003 ; Sayer, 2006 ). Less information is known about the reasons, reactions, and consequences in the short term, and the studies on maladaptive reactions shortly after the relationship dissolution are still few (Norona and Olmstead, 2017 ; Lee et al, 2020 ; Cope and Mattingly, 2021 ). Various models describe the process of dissolution of the couple (e.g., Sbarra and Emery, 2005 ; Rollie and Duck, 2006 ), and although it is difficult to indicate a defined period relating to the phase of the dissolution of the couple, previous research converges around a period of 4–6 months (Najib et al, 2004 ; Verhallen et al, 2019 ), ranging from 1 week (Mearns, 1991 ) to 12 months and beyond (Sprecher et al, 1998 ; Cope and Mattingly, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals may experience identity confusion (Slotter, Gardner & Finkel, 2010) and distressing rumination (Saffrey & Ehrenberg, 2007) in response to relationship dissolution. In addition, individuals may be emotionally and psychologically distressed as they try to understand and make sense of themselves without their partner (Cope & Mattingly, 2020). Couple communication styles that can increase risk of relationship dissolution are attack-attack, attack-withdraw and withdraw-withdraw (Christense, 1987;Greenberg & Johnson, 1988).…”
mentioning
confidence: 99%
“…These breakups are among the strongest predictors of depressive symptoms and negative consequences such as attempting suicide (Donald, Dower, Correa-Velez, & Jones, 2006). When people break up with others, they may lose their self-concept (Cope & Mattingly, 2020), have repetitive, lethargic days and develop negative viewpoints that discourage them from starting new relationships (Lewandowski, Aron, Bassis, & Kunak, 2006;Slotter, Emery, & Luchies, 2014;Slotter et al, 2010). Confusion in self-concept following a breakup is associated with emotional distress after the dissolution, which, to some extent, shows why breakups are painful (Boelen & van den Houte, 2010).…”
mentioning
confidence: 99%